A Robust Folk Theorem for the Prisoner's Dilemma - Jeffrey C. Ely; Juuso Valimaki (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1999)
We prove the folk theorem for the Prisoner's dilemma using strategies that are robust to private monitoring. From this follows a limit folk theorem: when players are patient and monitoring is sufficiently accurate, (but private and possibly independent) any feasible individually rational payoff can be obtained in sequential equilibrium. The strategies used can be implemented by finite (randomizing) automata.
Keywords: 330